Introductory botany : plants, people, and the environment - Berg, Linda R. 4 0 16; 5 (Australia : Thomson Brooks/Cole)
The overall theme of this introductory textbook is the role of plants in the biosphere - in keeping with that theme, related environmental issues are integrated into each chapter.--NHBS Environment Bookstore.
Includes bibliographical references.
Keywords: 2 -- 0; 6; Botany; 20; 2